STUDI KOMPARASI PEDAGANG KAKI LIMA GOR H. AGUS SALIM DENGAN PEDAGANG KAKI LIMA PANTAI PURUS KOTA PADANG - Widyawati, Endang - (STKIP PGRI Sumbar, 2014)
This study aims to get the data , process, analyze and discuss the comparative vendorsGOR H. Agus Salim Street Vendors Purus Beach.This type of research is classified inComparative Descriptive reasearch. This population research was vendors in GOR H.Agus Salim and street vendors Purus Beach . Samples were taken using the formulaproposed by Solvin samples used were 56 merchants , 28 respondents traders GORH. Agus Salim and 28 respondents traders Purus Beach . The data was collected usinga guided questionnaire , analysis used descriptive statistics using percentage formulaand test hypotheses .The results showed as follows : 1 ) there is no difference vendorsGOR capital H. Agus Salim street vendors Purus Beach , because -t_hitung < t_ (table) ( - 0.173 < 2.004 ) , 2 ) there is no difference in the type of merchandisevendors GOR H. Agus Salim street vendors Purus Beach , because -t hitung< t_tabel( -0.747 < 2.004 ) , 3 ) there is no difference in working hours hawkers GOR H. AgusSalim street vendors Beach Purus , because -t_hitung < t_tabel ( -0.441 < 2.004 ) , 4 )there is no income difference vendors GOR H. Agus Salim street vendors PurusBeach , because ât hitung< t_tabel ( -0.488 < 2.004 ) , where the capital , type ofmerchandise , hours and income vendors GOR H. Agus Salim street vendors PurusBeach no differences were so great .